'Spontaneous' volunteers? Factors enabling the Student Volunteer Army mobilisation following the Canterbury earthquakes, 2010–2011. (1st February 2021) - Nissen, Sylvia; Carlton, Sally; Wong, Jennifer H.K.; Johnson, Sam
Abstract: 'Spontaneous' volunteers have long been recognized for the distinct and important contribution they can have within disaster response and recovery. The emergence of the Student Volunteer Army (SVA) has featured as a success story of crisis volunteerism in international disaster response literature and as a potential blueprint for youth-centred post-disaster civic action. Drawing on in-depth interviews with people involved in the SVA, we provide a framework for understanding the factors that helped enable its mobilisation. In outlining these factors, many of which pre-date the emergence of the SVA, the paper demonstrates that the successful mobilisation of 'spontaneous' volunteers is not necessarily as spontaneous as the term suggests. Our analysis furthers understanding of the diversity of crisis volunteerism and has implications for disaster response practitioners, particularly in recognising the importance of networks of support which exist before and beyond disaster. Highlights: The Student Volunteer Army has featured as a success story of crisis volunteerism. This paper identifies seven interconnected factors that enabled its mobilisation. The study shows that crisis volunteerism is not always as 'spontaneous' as is sometimes suggested. We call for more diverse and dynamic understandings of post-disaster civic action.